Bilateral ectopia lentis with isolated lens coloboma in Marfan syndrome - Sahu, Sabin (GMS Ophthalmol Cases, 2016)
A rare case of bilateral ectopia lentis with isolated lens coloboma in Marfan syndrome is reported. A 21-year-old female presented with decreased vision in both eyes. Her unaided visual acuity was 20/200 and 20/400 in the right and left eye, respectively, improving to 20/40 with –4.5 DS/–3.0 DC x 10° correction in the right eye and 20/80 with –10.0 DS/–6.5 Dc x10° correction in the left eye. On slit lamp examination under mydriasis, both eyes revealed ectopia lentis with lens coloboma and stretched zonules. Fundus examination revealed pigmentary changes at the fovea. On systemic evaluation, she was diagnosed with Marfan syndrome. She was prescribed a refractive correction in form of a contact lens and kept under observation.